Recent Progress in Nonlinear Frequency Conversion of Optical Vortex Lasers - Liu, Jie; Duan, Yanmin; Li, Zhihong; Zhang, Ge; Zhu, Haiyong (Frontiers in Physics, 2022)
Optical vortices are optical fields that possess helical phase and orbital angular momentum, which have found the application in micromanipulation, optical communication, orbital angular momentum-entanglement, super-resolution imaging, metrology, etc. The urgent need for the wide spreading applications of vortex laser is to increase the wavelength versatility. In this paper, the nonlinear frequency conversion of vortex lasers with a focus on sum frequency generation, stimulated Raman scattering and optical parametric oscillator were meticulous reviewed. The characteristics of topological charge transfer and output beam profiles of different frequency conversion were discussed. As the precise tuning of optical fields in both temporal and spatial domain shall be the trend of future study, it’s our hope that this review shall serve as a reference for the coming research. Combing these techniques with the streaming methods to produce optical vortices, i. e. annular pump, off-axis pump, reflection mirror with defect spots, spherical aberration and birefringence, it’s advisable to expand the wavelength and fill the wavelength gap in the ultraviolet, visible and infrared band.